Saving Main Street : small business in the time of COVID-19 - Rivlin, Gary (Harper Business, an imprint of HarperCollins Publishers, 2022)
"Journalist Gary Rivlin looks at how COVID-19 and government policies affected businesses throughout the pandemic"--